A BRIEF HISTORY OF SUSTAINABLE DEVELOPMENT PRINCIPLES AND ITS IMPLEMENTATION IN INTERNATIONAL LAW AND INDONESIAN LAW - Agit Yogi Subandi (PRANATA HUKUM, 2022)
In the beginning, humans wanted change in life. Especially in terms of human thought which was centered on God or nature (Theocentric), then later shifted to being centered on humans themselves (Anthropocentric). However, with this change, humans actually destroy their own habitation, because they exploit nature for their own interests and this actually becomes self-destruction. Based on this, a concept emerged to balance what humans need with what nature wants (the concept of natural law), namely sustainable development. This concept continues to develop until now, but the manifestation of the concept seems difficult to apply in life in countries. Therefore